2023
DOI: 10.1021/jacs.3c04912
|View full text |Cite
|
Sign up to set email alerts
|

A General Photocatalytic Strategy for Nucleophilic Amination of Primary and Secondary Benzylic C–H Bonds

Madeline E. Ruos,
R. Garrison Kinney,
Oliver T. Ring
et al.

Abstract: We report a visible-light photoredox-catalyzed method that enables nucleophilic amination of primary and secondary benzylic C(sp 3 )−H bonds. A novel amidyl radical precursor and organic photocatalyst operate in tandem to transform primary and secondary benzylic C(sp 3 )−H bonds into carbocations via sequential hydrogen atom transfer (HAT) and oxidative radicalpolar crossover. The resulting carbocation can be intercepted by a variety of N-centered nucleophiles, including nitriles (Ritter reaction), amides, car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Isolated versus analytical yields for (A) literature-extracted Ni-catalyzed C–O couplings and (B) a reported photocatalytic C–H activation substrate scope . Common reasons for the discrepancies between the yields are given.…”
Section: Selecting a Reaction Performance Metric As An Output Variablementioning
confidence: 99%
“…Isolated versus analytical yields for (A) literature-extracted Ni-catalyzed C–O couplings and (B) a reported photocatalytic C–H activation substrate scope . Common reasons for the discrepancies between the yields are given.…”
Section: Selecting a Reaction Performance Metric As An Output Variablementioning
confidence: 99%
“…The results of luminescence quenching experiments showed that it should be the amine that initially quenches the photoexcited state 4CzIPN to form highly reducing photocatalyst, thus initiating the catalytic cycle. Moreover, recent research by the Doyle [ 18 ] group has also demonstrated that the organic photocatalyst CF 3 ‐4CzIPN also exhibited potent reducing properties when it interacted with reductive amines. Indeed, in the current four‐component radical aminocarbonylation of perfluoroalkyl iodides, the addition of N ‐cyclohexylmorpholine as additive produced superior results.…”
Section: Resultsmentioning
confidence: 99%
“…Photocatalytic transformation has attracted the ever-growing attention of chemists. Crucially, the transformations often needed the use of organic small molecules as photocatalysts (PC). While chemists have turned their attention to catalytic intermolecular additions by radical relay over several years, it is still of great significance to realize cyclization cascades by radical addition-based photocatalytic radical relay. Enlightened by the versatility of hydrogen-atom-abstraction (HAA) in radical chemistry, in this paper, we would like to develop a photocatalytic radical cyclization cascade that involved radical relay and the HAA process for preparing the privileged core pyrrolo­[1,2- a ]­indole from N -alkene-linked indoles. , Distinctively, the key intermediate A derived from the radical relay process would undergo a HAA process instead of an oxidative RPC pathway.…”
Section: Introductionmentioning
confidence: 99%